LaBa0.8Ca0.2Co2O5+δ cathode with superior CO2 resistance and high oxygen reduction activity for intermediate-temperature solid oxide fuel cells. (29th April 2022) - Gu, Hongxia; Su, Chao; Zhou, Chuan; Liu, Yang; Zhang, Yuan; Yang, Guangming; Zhou, Wei; Shao, Zongping
Abstract: The development of highly efficient cathode materials with durable performance and high resistance toward environmental impurity is crucial for realizing the practical applications of intermediate temperature - solid oxide fuel cells (SOFCs). Since CO2 as the oxidation product of hydrocarbons is unavoidable in the surrounding air atmosphere for SOFCs operating on hydrocarbon fuels, CO2 tolerance of the air electrode is a big concern. Herein, LaBa0.8 Ca0.2 Co2 O5+δ (LBCC) double perovskite is proposed as a promising cathode with superior CO2 tolerance and favourable oxygen reduction activity. It shows a relatively low area specific resistance of 0.128 Ω cm 2 at 600 °C in a CO2 -free synthetic air atmosphere, tested based on a symmetrical cell configuration (LBCC | Gd0.2 Ce0.8 O1.9 | LBCC). In addition, under open-circuit voltage condition, it can run stably for more than 120 h in the air containing 1% CO2 (1% CO2, 21% O2 and 78% N2 ) at 650 °C. More attractively, the LBCC shows high reversibility in performance by removing CO2 from air. An anode-supported single SOFC with thin film doped ceria electrolyte (∼25 μm) and LBCC cathode shows a favourable peak power density of 1063 mW cm −2 at 700 °C by using ambient air as the cathode atmosphere and hydrogen as the fuel. Highlights: LBCC double perovskite is studied as the cathode of intermediate-temperature SOFC. LBCC exhibits an excellent oxygen reduction activity. LBCC has an excellent ability to recover after being removed from CO2 atmosphere. LBCC cathode shows a favourable stability under 1% CO2 containing-air.